2013
DOI: 10.1002/cvde.201207042
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Subsurface Hybrid Material Growth on the Mechanical Properties of Atomic Layer Deposited Thin Films on Polymers

Abstract: The mechanical properties of atomic layer deposition (ALD) coatings play a key role in their long-term use as encapsulation barriers for organic-based, flexible, electronic devices. Nano-indentation characteristics and flexure testing of nanometer-scale alumina on polyamide 6 (PA6) films are investigated to determine the influence of a sub-surface hybrid layer formed during the ALD process. This hybrid layer is observed to affect the mechanical performance of the thin films, in particular at lower processing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…11,[26][27][28] For some applications, conductive fiber mats may have a mechanical advantage over planar films because fibers offer a multiplicity of parallel conduction pathways, so that many fractures are needed before failure. Recent reports show ALD coatings can enhance or degrade mechanical performance, depending on properties of the substrate and the coating.…”
Section: Mechanical Properties Of Azo Coated Nylon-6 Nonwovensmentioning
confidence: 99%
See 1 more Smart Citation
“…11,[26][27][28] For some applications, conductive fiber mats may have a mechanical advantage over planar films because fibers offer a multiplicity of parallel conduction pathways, so that many fractures are needed before failure. Recent reports show ALD coatings can enhance or degrade mechanical performance, depending on properties of the substrate and the coating.…”
Section: Mechanical Properties Of Azo Coated Nylon-6 Nonwovensmentioning
confidence: 99%
“…11,[26][27][28] For some applications, conductive fiber mats may have a mechanical advantage over planar films because fibers offer a multiplicity of parallel conduction pathways, so that many fractures are needed before failure. Recently, Sun et al 28 showed with nanoindentation that the critical strain required to induce crack formation increased with deposition temperature between 60 and 120 C for Al 2 O 3 ALD deposited on spun-cast nylon-6 films. Results are plotted in Fig.…”
Section: Mechanical Properties Of Azo Coated Nylon-6 Nonwovensmentioning
confidence: 99%
“…6−9 Organometallic precursors reacting with functional groups within the polymers form organic−inorganic hybrid materials in the subsurface regions of the polymer. 8 The concept of precursor infiltration has inspired new techniques to create organic−inorganic hybrid materials, including techniques such as multiple pulsed vapor phase infiltration, 10,11 sequential infiltration synthesis, 12,13 and sequential vapor infiltration (SVI).…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, ALD on polymers is often complicated by subsurface precursor diffusion, which is influenced by thermal expansion of the polymer as well as the detailed reaction between precursors and polymers. 4,9,10 Analyzing conductance in situ during ZnO ALD on different polymers and at different temperatures will therefore provide insight into nucleation and growth mechanisms needed to achieve well-controlled coatings on polymer surfaces in general.This work will demonstrate a simple in situ two-wire and four-wire conductance probe to investigate the nature of ZnO ALD nucleation and film coalescence on polymer and quartz fiber substrates. We characterize the performance of the in situ conductance probe and use it to explore chemical and physical mechanisms during nucleation of ZnO on various untreated and pretreated polymeric and ceramic fiber surfaces.…”
mentioning
confidence: 99%